Modeling the influence of tooling on the final shape of polymer composite parts - Kozlov, Mikhail Vladimirovich; Sheshenin, Sergey Vladimirovich; Makarenko, Irina Vitalievna; Belov, Dmitriy Aleksandrovich (Computational Continuum Mechanics, 2016)
Theoretical comparison of mechanical models used to describe the curing process of a composite with thermosetting binder is given. An approximation of the experimental dependence of the elastic modulus of a binder on temperature is demonstrated for a number of models. Constitutive relations of CHILE and Svanberg models are implemented as self-made computational modules for a finite element analysis package. Simulation of the curing of a composite spar section is carried out taking into account the tooling body. The required composite properties were obtained by the homogenization method. The significant feature of the simulation is accounting for mechanical and thermal contacts between the part and the tooling, which changes its state during the solution process. A mechanical interaction model that considers the transition from slipping to sticking at binder’s gelation point is proposed. Simulation of heating in an oven is accomplished by specifying the conditions of convection on the total free surface of the tooling and the part. For the curing cycle under consideration the dependence of the relative solution error on the value of the solution time step is obtained. Thus the optimal time step is chosen to minimize the computational cost and preserve the solution acceptable accuracy. This optimization is of importance because of long-duration simulations. The results of numerical simulation of a composite spar section are given. For tooling materials, steel, Invar, aluminum and composite were taken. Several types of deviations from the desired shape of the structure modeled were observed. It is shown that these deviations are caused by the binder shrinkage and the effect of thermal expansion of tooling, which contributes significantly to the distorted shape of a manufactured composite. The higher was the thermal expansion coefficient of tooling material, the higher distortions of the final structure were observed in numerical simulation. The simulations clearly demonstrate that the tooling made of both Invar and composite shows the best result in the context of the product quality.